Nursed in the desert: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This narrative follows a child raised in the harsh conditions of the desert, showcasing resilience and adaptability. It emphasizes the importance of environment and nurturing in character development.